2013
DOI: 10.1063/1.4810791
|View full text |Cite
|
Sign up to set email alerts
|

Probing electron acceleration and x-ray emission in laser-plasma accelerators

Abstract: International audienceWhile laser-plasma accelerators have demonstrated a strong potential in the acceleration of electrons up to giga-electronvolt energies, few experimental tools for studying the acceleration physics have been developed. In this paper, we demonstrate a method for probing the acceleration process. A second laser beam, propagating perpendicular to the main beam, is focused on the gas jet few nanosecond before the main beam creates the accelerating plasma wave. This second beam is intense enoug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Plasma density profiles were estimated using a Normarsky interferometer. A second laser pulse (300 mJ / 30 fs) was used as a machining beam to estimate where electrons are injected and where x-ray radiation is produced along the laser propagation axis [18,19].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Plasma density profiles were estimated using a Normarsky interferometer. A second laser pulse (300 mJ / 30 fs) was used as a machining beam to estimate where electrons are injected and where x-ray radiation is produced along the laser propagation axis [18,19].…”
Section: Resultsmentioning
confidence: 99%
“…x-ray emission regions using the method described in [18]. We have found that the plasma lengths, over which Betatron radiation is produced, were 1.5 ± 0.5 mm for the up-ramp density, and 2 ± 0.5 mm for the constant density cases.…”
Section: Slow Longitudinal Rampmentioning
confidence: 93%
See 2 more Smart Citations
“…In this paper, we used a plasma structure of a density depression with a tunable length and position to enhance the betatron radiation generated from LWFA via ionization injection. The density depression is produced by using a technique of transverse laser machining [36,37] that has been applied in the enhancement of relativistic harmonic generation [38], and the optimization of LWFA [39,40] and betatron radiation [41]. By utilizing the density depression in a proper position, the amplitude of the betatron oscillation is increased after the accelerated electron passing through the depression, and therefore a bright betatron x-ray beam has been produced with a significant enhancement both in the critical energy and the photon number.…”
Section: Introductionmentioning
confidence: 99%